Prognostic impact of primary tumor SUV(max) on preoperative (18)F-fluoro-2-deoxy-D-glucose positron emission tomography and computed tomography in endometrial cancer and uterine carcinosarcoma - Yahata, Tamaki (Mol Clin Oncol, 2016)
The objective of the present study was to investigate the usefulness of the maximum standardized uptake value (SUV(max)) of the primary tumor on preoperative (18)F-fluoro-2-deoxy-D-glucose (FDG) positron emission tomography and computed tomography (PET/CT) as a prognostic indicator in patients with endometrial neoplasms. A total of 75 patients with endometrial cancer or uterine carcinosarcoma who underwent surgical treatment were included in the present study. All patients underwent preoperative PET/CT, and the correlation between the SUV(max) of the primary tumor and clinical outcomes was analyzed. The SUV(max) was significantly higher in patients with stage II/III disease, a histology of grade 3 endometrioid adenocarcinoma and carcinosarcoma, a positive lymph node (LN) status, positive lymph-vascular space involvement (LVSI), and deep (≥1/2) myometrial invasion. Receiver operating characteristic curve analysis revealed that the optimal cut-off values of SUV(max) for predicting a positive LN, LVSI and deep myometrial invasion were 7.49, 6.45 and 6.45, respectively. The overall survival (OS) and progression-free survival (PFS) of patients with a high SUV(max) were significantly lower compared with those of patients with a low SUV(max) using the cut-off value of 7.30. However, no significant difference was observed in the OS or PFS between the high and low SUV(max) groups when analyzed in carcinosarcoma patients alone. Finally, multivariate analyses demonstrated that the SUV(max) of the primary tumor was an independent prognostic factor for impaired PFS in 55 endometrioid adenocarcinoma patients; however, not in all patients, including those with carcinosarcoma. The present findings demonstrated that the SUV(max) of the primary tumor may be a useful biomarker for predicting clinical outcomes of patients with endometrial cancer, although its prognostic impact appears to be limited in patients with uterine carcinosarcoma.